2021
DOI: 10.1021/acs.jpca.1c02923
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structure and Excited States of the Collision Reaction O(3P) + C2H4: A Multiconfigurational Perspective

Abstract: We present a study of the O­(3P) + C2H4 scattering reaction, a process that takes place in the interstellar medium and is of relevance in atmospheric chemistry as well. A comprehensive investigation of the electronic properties of the system has been carried out based on multiconfigurational ab initio CASSCF/CASPT2 calculations, using a robust and consistent active space that can deliver accurate potential energy surfaces in the key regions visited by the system. The paper discloses detailed description of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Following the definition given in eq and expressing the electronic wavefunction as the ratio of the molecular and nuclear wavefunctions, from eq , the TDVP reads where S ( x , t ) is the phase of the nuclear wavefunction. It is easy to see that imposing the gauge condition A ( x , t ) = 0 yields an integral equation that defines S ( x , t ) in terms of the nuclear momentum fieldthat is, the first term on the right-hand side of eq .…”
Section: Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the definition given in eq and expressing the electronic wavefunction as the ratio of the molecular and nuclear wavefunctions, from eq , the TDVP reads where S ( x , t ) is the phase of the nuclear wavefunction. It is easy to see that imposing the gauge condition A ( x , t ) = 0 yields an integral equation that defines S ( x , t ) in terms of the nuclear momentum fieldthat is, the first term on the right-hand side of eq .…”
Section: Numerical Resultsmentioning
confidence: 99%
“…where S(x, t) is the phase of the nuclear wavefunction. It is easy to see that imposing the gauge condition A(x, t) = 0 yields an integral equation that defines S(x, t) in terms of the nuclear momentum field 59 �that is, the first term on the right-hand side of eq 40.…”
Section: Nonadiabatic Case: Dynamics On Time-dependent Pessmentioning
confidence: 99%
“…In this case, the interaction potential V (r, R,t) depends on μ(r, R), the molecule electric dipole moment, and on E(t), the external time-dependent electric field. In some situations [154][155][156][157][158][159][160][161][162][163][164] , the relativistic correction due to the geometrydependent spin-orbit coupling ĤSOC (x, R) can be included in the system Hamiltonian, where the variable x = [r, σ] accounts for the electronic spin σ as well as for the electronic positions r.…”
Section: The Exact Factorization Frameworkmentioning
confidence: 99%
“…More experimental studies can be found for larger systems, in particular by Casavecchia and coworkers who studied ISC in several reactions between atomic O( 3 P) with several unsaturated hydrocarbons 22 . The ISC in one of these reactions, O( 3 P)+C 2 H 4 , motivated numerous theoretical studies on the electronic stucture 23 and reaction dynamics studies using TSH 24,25 and NA-TST 26 . Although theory could qualitatively explain the experimental observation, it was not able to reproduce quantitatively the experimental branching ratio between products.…”
Section: Introductionmentioning
confidence: 99%